A SPECIFIC OF UKRAINIAN TELEVISION FEATURES IMPACT OF POLITICAL ADVERTISING ON TARGET AUDIENCE (ON THE СOMMERCIALS 2014) - Мадрига, Т. Б. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Idea, 2019)
This paper attempts to evaluate the use of methods of information-psychological influence on the electorate that were used in the television political advertising, which was broadcast on Ukrainian television channels during the presidential electioncampaign in 2014.